Functional Investigations of Thromboxane Synthase (CYP5A1) in Lipid Bilayers of Nanodiscs. Issue 6 (12th March 2014) - Das, Aditi; Varma, Snehita Sri; Mularczyk, Christopher; Meling, Daryl D.
Abstract CYP5A1 is a membrane‐associated cytochrome P450 that metabolizes the cyclooxygenase product prostaglandin (PGH2) into thromboxane A2 (TXA2), a potent inducer of vasoconstriction and platelet aggregation. Although CYP5A1 is an ER‐bound protein, the role of membranes in modulating the thermodynamics and kinetics of substrate binding to this protein has not been elucidated. In this work, we incorporated thromboxane synthase into lipid bilayers of nanodiscs for functional studies. We measured the redox potential of CYP5A1 in nanodiscs and showed that the redox potential is within a similar range of other drug‐metabolizing P450 enzymes in membranes. Further, we showed that binding of substrate to CYP5A1 can induce conformational changes in the protein that block small‐molecule ligand egress by measuring the kinetics of cyanide binding to CYP5A1 as a function of substrate concentration. Notably, we observed that sensitivity to cyanide binding was different for two substrate analogues, U44069 and U46619, thus indicating that they bind differently to the active site of CYP5A1. We also characterized the effects of the different lipids on CYP5A1 catalytic activity by using nanodiscs to create unary, binary, and ternary lipid systems. CYP5A1 activity increased dramatically in the presence of charged lipids POPS and POPE, as compared to the unary POPC system. These results suggest the importance of lipid composition on modulating the activity of CYP5A1 to increase thromboxane formation.